PERBANDINGAN DAYA HAMBAT MADU SEULAWAH DENGAN MADU TRUMON TERHADAP Staphylococcus aureus SECARA IN VITRO - Fadhmi ,; Mudatsir ,; Essy Syaukani (Biotik, 2015)
This research aimed to determine the ratio inhibition of forest honey Seulawah and Trumon on Staphylococcus aureus in vitro. The research was conducted in July to August 2014 in the Laboratory of Microbiology Academy of Health Analyst (AAK) in Banda Aceh. This research used acompletely randomized factorial designwith treatmentconsisting ofnegative control(NaCl 0,85% was given), positive control(ciprofloxacin antibiotics was given), foresthoneywitha concentrationof 25%, 50%, 75% and 100% with six replications. Data were analyzed by using Analysis of Variance (ANOVA). The results showed that the forest honey Seulawah and Trumon had different inhibition on Staphylococcus aureus in vitro. The inhibition of forest honey Seulawah was higher than the inhibition of forest honey Trumon.